EVALUATION OF ENDOGENOUS FAECAL CORTISOL AS A NON INVASIVE ASSESSMENT OF STRESS IN FREE RANGING WILD PIGS (Sus scrofa) - Boon Allwin; M.G. Jayathangaraj; M. Palanivelrajan; M. Raman (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was carried out to assess the faecal cortisol concentration in wild pigs entering the agricultural fields around the adjoining areas of Mudumalai Tiger reserve (MTR), Sathyamangalam Tiger reserve (STR) and Anamalai tiger reserve (ATR) of Tamil Nadu, India, in order to arrive at the baseline values contributing to the stress factors. Faecal samples collected from wild pigs in each of these areas were subjected to Enzyme Linked Immuno Sorbent Assay (ELISA) for estimation of faecal cortisol level and the mean faecal cortisol concentration of wild pigs were arrived. The occurrences of conflict, lack of food and water availability, temperature, rainfall and prey prevalence played an important role to their stress quotients. Suitable management related measures were recommended. The findings demonstrated that fecal glucocorticoid assays provide an index of physiological stress in wild pigs. These techniques may prove useful in addressing conservation issues and additionally being non invasive.